A Large Intra-Abdominal Hiatal Hernia as a Rare Cause of Dyspnea. (1st July 2015) - Sahin, Cem; Akın, Fatih; Cullu, Nesat; Özseker, Burak; Kirli, İsmail and Altun, İbrahim
Abstract : Giant hiatal hernias, generally seen at advanced ages, can rarely cause cardiac symptoms such as dyspnea and chest pain. Here, we aimed to present a case with a large hiatal hernia that largely protruded to intrathoracic cavity and caused dyspnea, particularly at postprandial period, by compressing the left atrium and right pulmonary vein. We considered presenting this case as large hiatal hernia is a rare, intra-abdominal cause of dyspnea.